Automatic Constraint Partitioning to Speed Up CLP Execution - Pereira, Marluce Rodrigues; Vargas, Patricia Kayser; Castro, Maria Clicia Stelling de; Franca, Felipe M. G.; Dutra, Inas de Castro (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2007)
Speedup in distributed executions of Constraint Logic Programming (CLP) applications are directed related to a good constraint partitioning algorithm. In this work we study different mechanisms to distribute constraints to processors based on straightforward mechanisms such as Round-Robin and Block distribution, and on a more sophisticated automatic distribution method, Grouping-Sink, that takes into account the connectivity of the constraint network graph. This aims at reducing the communication overhead in distributed environments. Our results show that Grouping-Sink is, in general, the best alternative for partitioning constraints as it produces results as good or better than Round-Robin or Blocks with low communication rate.